2015
DOI: 10.1016/j.meegid.2014.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carbapenem-resistant Enterobacteriaceae in an Italian setting: Report from the trench

Abstract: The spread of carbapenem resistant Enterobacteriaceae (CRE) has recently become a matter of concern in public health, mainly due to the wide distribution of carbapenemase genes. Italy is a country considered endemic for the spread of blaKPC Klebsiella pneumoniae (KP). The aim of this study was to depict the epidemiological trend of CRE in one Italian hospital over a long period (3 years surveillance, from May 2011 to April 2014). Based on defined MIC cut-off for specific carbapenems, 164 strains isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
(32 reference statements)
4
12
0
Order By: Relevance
“…The correct identification of carbapenemase genes is also necessary to address therapeutic options using the newer beta-lactam-beta-lactamase inhibitors with activity against serine-based carbapenemases (e.g., avibactam has no activity against MBLs, varborbactam covers only KPCs, and relebactam may have a different degree of efficacy related to the presence of particular genes) (24). Moreover, molecular confirmation of carbapenemase gene carriage may be useful to correctly identify CROs expressing low MICs for carbapenems, as sometimes happens for bla VIM and bla OXA-48 (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The correct identification of carbapenemase genes is also necessary to address therapeutic options using the newer beta-lactam-beta-lactamase inhibitors with activity against serine-based carbapenemases (e.g., avibactam has no activity against MBLs, varborbactam covers only KPCs, and relebactam may have a different degree of efficacy related to the presence of particular genes) (24). Moreover, molecular confirmation of carbapenemase gene carriage may be useful to correctly identify CROs expressing low MICs for carbapenems, as sometimes happens for bla VIM and bla OXA-48 (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys conducted in Italy have shown that the KPC‐type enzymes most commonly encountered are KPC‐3 followed by KPC‐2 . The bla VIM gene has been reported with a minor prevalence . A survey conducted in 2011 involving 25 Italian cities, distributed throughout the nation and covering most Italian regions including two hospitals in Apulia, Southern Italy, reported that among 13 749 clinical isolates of Enterobacteriaceae , carbapenemases were found in 2.0% of the isolates and K. pneumoniae contributed to the majority of carbapenem‐resistant Enterobacteriaceae (CRE) (86.7%) representing the 11.9% of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the spread of carbapenem‐resistant K. pneumoniae has dramatically increased since 2009, the KPC‐3 variant being the predominant clone circulating in Italy . In this country, there are hotspot data on the diffusion and type of carbapenemases‐producing Enterobacteriaceae and K. pneumoniae in particular, and few of these data come from Apulia and Basilicata .…”
mentioning
confidence: 99%
“…Sporadic outbreaks of Pseudomonas aeruginosa containing bla VIM have been reported in South America (11,12) and in Chicago (13). One paper by Barbarini and colleagues described the changing epidemiology of CPOs in an Italian hospital over a 3-year period, in which 44 bla VIM -positive K. pneumoniae isolates were reported (14). Another study reported a single isolate of sequence type 258 (ST258) bla KPC K. pneumoniae that was also found to coexpress bla VIM in addition to other resistance determinants (15).…”
mentioning
confidence: 99%